Prokaryotic variables from a indoor-mesocosm experiment measured during the winter in the Northern Bothnian Sea - Verma, Ashish; Amnebrink, Dennis; Pinhassi, Jarone; Wikner, Johan (PANGAEA, 2023)
The primary data was collected during the indoor-mesocosm experiment conducted in March 2020 at Umea Marine Science Centre, Umea University, Sweden situated in the Northern Bothnian Sea (63° 34ˈN, 19° 50ˈE). A full factorial experiment was set with temperature and the addition of nutrients as treatment factors with a natural pelagic food web containing all trophic levels except fish. A total of four experimental treatments were set up with three replicates each: C, control (1°C, no additions); N (1°C,+ nutrients); T (10°C, no additions) and TN (10°C, + nutrients). For each treatment, eight different samplings were done in triplicates. The variables in the data include the prokaryotic abundance (PA), growth (PG), respiration (PR), specific prokaryotic respiration (ρ), specific growth rates (µ), growth efficiency (PGE), dissolved organic carbon (DOC), total dissolved phosphorus (TDP) and total dissolved nitrogen (TDN).
Keywords: 16S metabarcoding; growth rate; mesocosm experiment; prokaryote; prokaryotic abundance; Respiration